SNCA (α-synuclein)-induced toxicity in yeast cells is dependent on sirtuin 2 (Sir2)-mediated mitophagy - Marques, Belém Sampaio (2012)
SNCA (α-synuclein) misfolding and aggregation is strongly associated with both idiopathic and familial forms of Parkinson disease (PD). Evidence suggests that SNCA has an impact on cell clearance routes and protein quality control systems such as the ubiquitin-proteasome system (UPS) and autophagy. Recent advances in the key role of the autosomal recessive PARK2/PARKIN and PINK1 genes in mitophagy, highlighted this process as a prominent new pathogenic mechanism. Nevertheless, the role of autophagy/mitophagy in the pathogenesis of sporadic and autosomal dominant familial forms of PD is still enigmatic. The yeast Saccharomyces cerevisiae is a powerful “empty room” model that has been exploited to clarify different molecular aspects associated with SNCA toxicity, which combines the advantage of being an established system for aging research. The contribution of autophagy/mitophagy for the toxicity induced by the heterologous expression of the human wild-type SNCA gene and the clinical A53T mutant during yeast chronological life span (CLS) was explored. A reduced CLS together with an increase of autophagy and mitophagy activities were observed in cells expressing both forms of SNCA. Impairment of mitophagy by deletion of ATG11 or ATG32 resulted in a CLS extension, further implicating mitophagy in the SNCA toxicity. Deletion of SIR2, essential for SNCA toxicity, abolished autophagy and mitophagy, thereby rescuing cells. These data show that Sir2 functions as a regulator of autophagy, like its mammalian homolog, SIRT1, but also of mitophagy. Our work highlights that increased mitophagy activity, mediated by the regulation of ATG32 by Sir2, is an important phenomenon linked to SNCA-induced toxicity during aging.